Wild Animals Flashcard-Based AR as an Early Reading Game for Young Children - Dian Ramadhani Padwika; Sri Sumarni; Windi Dwi Andika; Zahra Alwi; Muhammad Arry Erpapalemlah (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Wild animal material has been introduced by teachers and parents only in the traditional. Early reading can be challenging since it might be difficult to recognize new words. Technology has been used to this issue in the form of flashcard with augmented reality (AR). This study aims to develop a flashcard material for wild animals based on augmented reality for children aged (5-6) years in Kayu Agung which has been tested for validity and practicality. The research method used in this research was Research Development (RD) research. The research procedure was Rowntree and formative evaluation Tessmer. The formative evaluation stage of Tessmer consisted of self-evaluation, expert review, one-to-one evaluation, and small group evaluation. The results showed the wild animals flashcard-based AR was developed had met the valid and practical criteria and was suitable to children aged (5-6) as an early reading game years in Kayu Agung